2001
DOI: 10.2307/3069408
|View full text |Cite
|
Sign up to set email alerts
|

The Strategic Context of External Network Ties: Examining the Impact of Director Appointments on Board Involvement in Strategic Decision Making.

Abstract: This study examines how external network ties determine a board's ability to contribute to the strategic decision making process. Although the simple number of director appointments to other boards does not affect board monitoring or advice on strategy, appointments that can provide directors with relevant strategic knowledge and perspective do predict such involvement. In effect, the strategic context of social network ties, not simply the number of ties, is an important influence on corporate governance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
601
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 933 publications
(629 citation statements)
references
References 92 publications
18
601
0
10
Order By: Relevance
“…This finding confirmed Ingley and Van der Walt (2001) study, which stated that level of educational qualification will function as a strategic resource. It will also act as a mix of diverse characteristics that help in executing the governance function (Carpenter & Westphal, 2001). Therefore, our findings translating into three theoretical propositions…”
Section: Discussion Of Findings and Theoretical Propositionsmentioning
confidence: 99%
“…This finding confirmed Ingley and Van der Walt (2001) study, which stated that level of educational qualification will function as a strategic resource. It will also act as a mix of diverse characteristics that help in executing the governance function (Carpenter & Westphal, 2001). Therefore, our findings translating into three theoretical propositions…”
Section: Discussion Of Findings and Theoretical Propositionsmentioning
confidence: 99%
“…Prior studies also have shown that board of director networks play a major role to provide an important source of information (Horton et al, 2012;Chenhall, Hall & Smith, 2010;Carpenter & Westphal, 2001). Eventually, this will support the company's strategic decisions and control direction (Durbach & Parker, 2009) and enhance the board's advising role (Stuart & Yim, 2010).…”
Section: Related Literaturementioning
confidence: 99%
“…This will damage prospects in the labour market for directors and managers (Carpenter & Westphal, 2001). Thus, the selection for competence directors is essential for companies in order to succeed.…”
Section: Related Literaturementioning
confidence: 99%
“…Social capital can be defined as a sum of actual and potential resources that are available through a person's relationships with others (Nahapiet & Ghoshal, 1998). The human and social capitals that directors bring to an organization can influence strategic decisions of the organization (Carpenter & Westphal, 2001;Jensen & Zajac, 2004).…”
Section: Board Of Directors As An Integration Mechanismmentioning
confidence: 99%
“…The human capital of an organization can be enhanced by appointing outside directors (Bailey & Helfat, 2003;Carpenter & Westphal, 2001). Outside directors have distinct experiences in different fields.…”
Section: Number Of Outside Directorsmentioning
confidence: 99%